Thermal Radiation Effects on MHD Free Convection Flow Past an Impulsively Started Vertical Plate with Variable Surface Temperature and Concentration (Journal of Naval Architecture and Marine Engineering, 2009)
Thermal radiation effects on hydromagnetic free convection flow past an impulsively started vertical plate with variable surface temperature and concentration is analyzed, by taking into account the heat due to viscous dissipation. The governing boundary layer equations of the flow field are solved by an implicit finite difference method of Crank-Nicholson type. A parametric study is performed to illustrate the influence of radiation parameter, magnetic parameter, Grashof number, Prandtl number, Eckert number on the velocity, temperature and concentration profiles. Also, the local and average skin-friction coefficient, Nusselt number and Sherwood number are presented graphically. The numerical results reveal that an increase in thermal radiation reduces both the velocity and temperature in the boundary layer and a rise in viscous dissipation accelerates the flow.  Key words: Thermal radiation, MHD, viscous dissipation, vertical plate. DOI: 10.3329/jname.v5i2.2694   Journal of Naval Architecture and Marine Engineering 5(2)(2008) 57-70